Catalyst Characteristics and Performance of Silica-Supported Zinc for Hydrodeoxygenation of Phenol - Hamed Pourzolfaghar; Faisal Abnisa; Wan Mohd Ashri Wan Daud; Mohamed Kheireddine Aroua; Teuku Meurah Indra Mahlia (Energies, 2020)
The present investigation aimed to study the physicochemical characteristics of supported catalysts comprising various percentages of zinc dispersed over SiO2. The physiochemical properties of these catalysts were surveyed by N2 physisorption (BET), thermogravimetry analysis (TGA), H2 temperature-programmed reduction, field-emission scanning electron microscopy (FESEM), inductively coupled plasma-optical emission spectrometry (ICP-OES), and NH3 temperature-programmed desorption (NH3-TPD). In addition, to examine the activity and performance of the catalysts for the hydrodeoxygenation (HDO) of the bio-oil oxygenated compounds, the experimental reaction runs, as well as stability and durability tests, were performed using 3% Zn/SiO2 as the catalyst. Characterization of silica-supported zinc catalysts revealed an even dispersion of the active site over the support in the various dopings of the zinc. The acidity of the calcinated catalysts elevated clearly up to 0.481 mmol/g. Moreover, characteristic outcomes indicate that elevating the doping of zinc metal led to interaction and substitution of proton sites on the SiO2 surface that finally resulted in an increase in the desorption temperature peak. The experiments were performed at temperature 500 °C, pressure 1 atm; weight hourly space velocity (WHSV) 0.32 (h−1); feed flow rate 0.5 (mL/min); and hydrogen flow rate 150 (mL/min). Based on the results, it was revealed that among all the prepared catalysts, that with 3% of zinc had the highest conversion efficiency up to 80%. However, the selectivity of the major products, analyzed by gas chromatography flame-ionization detection (GC-FID), was not influenced by the variation in the active site doping.